SYNERGISTIC ACTION OF INSECTOACARICIDE COMPOSITIONS BASED ON BITTER ALMOND SEEDS - Tukhtaev Khakim Rahmanovich; Khamidov Orifjon Jahongirovich; Mirzaeva Adolat Usmonboevna (European Journal of Agricultural and Rural Education, 2022)
The article presents data on the physicochemical properties of a complex composition in the form of powder and suspension in various concentrations based on bitter almond seeds. For the powder and suspension, the particle sizes, electrical conductivity of the solution, surface tension, and biological activity were determined. The complex composition contains seeds of bitter almonds, extracts of bitter wormwood, onion, garlic, laundry soap, kaolin adsorbent and cornflour. A complex composition based on bitter almond seeds is effective against Argas persicus mites under the studied conditions. The studies were carried out on ticks Argas persicus at various stages of ontogeny, collected from birds and farm animals. The death of ticks at different concentrations was studied. Starting at a concentration of 0.5%, the death of mites is observed. From 1.0 to 2.5% concentration, the death of ticks ranges from 32±0.4% to 56±0.3%. More effective concentrations turned out to be 5-10%, where the death of mites reaches 84 ± 0.2%. The composition based on plant extracts is an environmentally friendly, safe insectoacaricide